FORMATION OF NITROGEN OXIDES AT TWO-STAGE NATURAL GAS BURNING - I. G. Zhikhar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A kinetic model of natural gas burning has been developed. Calculated investigation of formation and reduction of nitrogen oxides at two-stage natural gas burning has been executed on the basis of the proposed model.